Budidaya Terumbu Karang yang Dipimpin oleh Komunitas: Studi Kasus dari Pulau Pahawang, Indonesia - Winati Nurhayu; Sarah Azmi; Novriadi; Yanti Ariyanti; Dian Anggria Sari (Jurnal Penelitian Pendidikan IPA, 2025)
Coral reefs play a crucial role in Indonesia's coastal ecosystems, offering ecological and economic benefits. Pahawang Island, Lampung, presents a potential site for sustainable coral reef farming. However, destructive fishing practices, such as fish bombing in 2000, caused severe reef damage, prompting a cultivation initiative aimed at restoration and sustainable utilization. This study, conducted in 2024, explored the impacts and challenges of coral reef farming on Pahawang Island using surveys and focus group discussions. Data collection involved interviews with 100 residents, including coral farmers and village officials, and discussions with representatives from BUMDes, POKDARWIS, village officials, and coral reef traders. The Business Model Canvas and SWOT analysis were employed for evaluation. Hamlet had significantly stronger positive perceptions of coral reef farming (p-value = 0.037), while Pahawang Hamlet residents emphasized its challenges (p-value = 0.018). The findings also highlighted that many coral reef farmers had yet to fully implement all aspects of their business models. This study underscores the need for targeted interventions to address challenges and enhance sustainable coral reef farming practices.